Morir con dignidad: Estudio sobre voluntades anticipadas Dying with dignity: A study of living wills - Cristina Nebot; Blas Ortega; José Joaquín Mira; Lidia Ortiz (Elsevier, 2010)
Objetivo: Describir el perfil de quienes han ejercido su derecho a expresar voluntades anticipadas, analizar la actitud y el conocimiento de los médicos ante ellas, y comparar las normas que regulan este derecho entre comunidades autónomas. Método: Estudio descriptivo que incluye análisis mediante muestreo sistemático de 931 registros de voluntades anticipadas en la Comunidad Valenciana, encuesta en papel estructurada y autoadministrada a una muestra de 84 médicos de servicios de urgencias y unidades de cuidados intensivos (tasa respuesta del 45%), y comparación de la legislación autonómica que regula las voluntades anticipadas. Resultados: Un 1,6‰ mayores de 16 años han inscrito voluntades anticipadas (relación mujer/hombre de 1,8/1), la mayoría (73,8%) utilizando un documento previamente redactado por una determinada confesión religiosa. Limitar el esfuerzo terapéutico (99%) y obtener fármacos para aliviar el dolor (98%) son las razones habituales para inscribir voluntades anticipadas. Pese a que 61 (72,6%) facultativos atendían con frecuencia a pacientes en situación terminal, sólo el 6% consultaron el registro de voluntades anticipadas en estos casos. El 28% no supo cómo consultar este registro. Hay una amplia variabilidad entre comunidades respecto a la edad para otorgar voluntades anticipadas, cómo actuar en caso de embarazo de la solicitante, ante quién otorgar voluntades anticipadas y el número de puntos en que es posible dejar constancia de estas voluntades Conclusiones: La mayoría de los otorgantes de voluntades anticipadas profesan una determinada confesión y rechazan que se les practiquen determinados tratamientos. La mayoría de los profesionales no comprueba si los enfermos en situación crítica han otorgado voluntades anticipadas. La diversidad de criterios entre comunidades complica el ejercicio del derecho a expresar estas voluntades. Objective: To describe the profile of persons who exercise their right to draw up a living will, to analyze physicians´ knowledge of living wills and attitudes toward them, and to compare the regulations pertaining to this right in the distinct autonomous regions of Spain. Method: A descriptive study that included an analysis of a systematic sample of 931 living wills registered in the autonomous region of Valencia (Spain), a self-administered structured questionnaire administered to a sample of 84 physicians working in emergency departments and intensive care units (45% response rate), and a comparison of the regional legislation covering living wills. Results: A total of 1.6% of inhabitants aged 16 or over had registered a living will (female/male ratio: 1.8/1). Most (73.8%) used a standard document drawn up by a particular religious faith. The most common reasons for writing a living will were to limit therapeutic efforts (99%) and obtain pain-relieving drugs (98%). Although 61 physicians (72.6%) frequently attended the terminally ill, only 6% consulted the register of living wills in these situations and 28% did not know how to consult this register. There is wide variation among regions in the minimum age for registering a living will, in the procedure to be followed if the signer is pregnant, in designating a person as having the authority to make a living will, and in the number of registration points available to deposit livingwills. Conclusions: Most persons registering a living will are healthy individuals with a particular religious faith who reject certain treatments. Most health professionals do not check whether critically ill patients have made a living will. Exercising the rights contained in living wills is complicated by the diversity of criteria among different regions.